Debating the Arctic during the Ukraine Crisis – comparing Arctic state identities and media discourses in Canada and Norway. Issue 2 (3rd July 2017) - Burke, Danita Catherine; Rahbek-Clemmensen, Jon
Abstract: Previous studies have argued that domestic factors, including each state's Arctic state identities, may explain why some Western states (e.g. Canada) have been more critical of Russia in the Arctic than others (e.g. Norway). The present study analyses part of the link between Arctic state identities and foreign policy by showing that these identifications affected domestic media discourses about the Arctic in Canada and Norway during the first years (2014–2016) of the Crisis. Canada's territorial identification made it difficult for the newly elected Trudeau government to push for a less assertive course vis-à-vis Russia. In Norway, the strong economic discourse coloured early debates about the crisis, but after the widening of economic sanctions against Russia in the summer of 2014, territorial discourses played a more important role. The article thus illustrates that Arctic state identities shape media debates, but that the identifications themselves can change. In general, the article advocates for a comparative approach towards the analysis of Arctic state identities.